Differential alternative splicing coupled to nonsense-mediated decay of mRNA ensures dietary restriction-induced longevity - Syed Shamsh Tabrez (Nature Portfolio, 2017)
Alternative splicing coupled to nonsense-mediated decay (AS-NMD) is a conserved mechanism for post-transcriptional gene regulation. Here, the authors provide evidence that AS-NMD is enhanced during dietary restriction (DR) and is required for DR-mediated longevity assurance in C. elegans.